Anak laki-laki usia 4 tahun dengan paraparesis lower motor neuron, gizi kurang, pendek, dan masalah makan di RS tipe B: sebuah laporan kasus - Fitriana Melinda; Made Ratna Dewi (Intisari Sains Medis, 2021)
Background: Paralysis is a symptom of various diseases, disorders, or certain conditions, ranging from mild to severe and can be caused by infectious processes, trauma, malignancies, autoimmune diseases, and other abnormal processes. Eating problems in children is one of the developmental disorders that can occur in healthy infants or children. Eating problems have the potential to cause cognitive and behavioral disorders, and are associated with anxiety disorders and eating disorders in children, adolescents, and young adults. Case description: A 4 years 2 months old male, complained not being able to walk and his legs shrinking since 2 weeks of SMRS. His male cousin has experienced paralysis of the right leg since the 3rd grade of elementary school. There were multiple enlarged right inguinal lymph nodes accompanied by refusal to take meal for the past 3 months. Neurological examination found normal energy in all four extremities but decreased patellar and achilles reflex. Body weight (BW) was 11 kg, body length (BL) 94 cm, BW/BL (-3) - (-2) SD (wasted). Leukocytes 6.4/ul, hemoglobin 11.0 g/dl, hematocrit 33.3%, MCV 69.4 fl, MCH 22.9 pg, MCHC 33.0 g/L, platelets 396.000 /ul, ESR 41 mm / hours, CRP 11 mg/L and CK 1,441 U/L. Radiological examination of lumbosacral photo showed the impression of paraspinal muscle spasm. The patient diagnose with lower motor neuron paraparesis. Conclusion: Handling of patients with eating problems and LMN paraparesis is given non-medical management by meeting fluid needs, nutrition according to patient needs and education about feeding rules to the patient's parents, consultation with psychologists, and medical rehabilitation seek treatment. improvement of eating problems and medical problems in the form of weak legs more optimally.   Latar belakang: Kelumpuhan adalah gejala dari berbagai penyakit, kelainan, atau kondisi tertentu, mulai dari yang ringan sampai berat, yang disebabkan oleh proses infeksi, trauma, keganasan, penyakit autoimun, dan proses abnormal lainnya. Masalah makan pada anak merupakan salah satu gangguan perkembangan yang dapat terjadi pada bayi atau anak sehat. Selain itu, masalah makan berpotensi menyebabkan gangguan kognitif dan perilaku, serta dikaitkan dengan gangguan cemas dan kelainan makan pada anak, remaja, dan dewasa muda. Deskripsi kasus: Anak laki-laki berusia 4 tahun 2 bulan, keluhan tidak bisa berjalan dan kaki mengecil sejak 2 minggu SMRS. Kakak sepupu laki-laki dari ibu pasien mengalami kelumpuhan kaki kanan sejak kelas 3 SD. Ditemukan adanya pembesaran kelenjar getah bening inguinal dekstra multipel disertai tidak mau makan sejak 3 bulan lalu. Pemeriksaan neurologis didapatkan tenaga normal pada keempat ekstremitas namun penurunan refleks fisiologis kniepeesreflex (KPR) dan achillespeesreflex (APR). Status antropometri yaitu BB 11 kg, PB 94 cm, BB/PB (-3)-(-2) SD (wasted). Leukosit 6.4 /ul, hemoglobin 11.0 g/dl, hematokrit 33,3%, MCV 69,4 fl, MCH 22,9 pg, MCHC 33,0 g/L, trombosit 396.000/ul, LED 41 mm/jam, CRP 11 mg/L dan CK 1,441 U/L. Radiologi lumbosakral antero-posterior/lateral didapatkan kesan paraspinal muscle spasm. Pasien didiagnosis paraparesis lower motor neuron (LMN). Simpulan: Penanganan pasien dengan anak dengan masalah makan dan paraparesis LMN diberikan penatalaksanaan non-medikamentosa dengan pemenuhan kebutuhan cairan, nutrisi sesuai kebutuhan pasien dan edukasi mengenai feeding rules kepada orang tua pasien, konsultasi dengan psikolog, serta rehabilitasi medik untuk mengupayakan perbaikan masalah makan dan masalah medis berupa kaki lemas dengan lebih maksimal.